The development of memory maintenance strategies: training cumulative rehearsal and interactive imagery in children aged between 5 and 9 - Miller, Sadie; McCulloch, Samantha; Jarrold, Christopher (Frontiers in Psychology, 2015)
The current study explored the extent to which children above and below the age of 7 years are able to benefit from either training in cumulative rehearsal or in the use of interactive imagery when carrying out working memory tasks. Twenty-four 5- to 6-year-olds and 24 8- to 9-year olds were each assigned to one of three training groups who either received cumulative rehearsal, interactive imagery, or passive labelling training. Participants’ ability to maintain material during a filled delay was then assessed, and the nature of the distraction that was imposed during this delay was varied to shed further light on the mechanisms that individuals used to maintain the memoranda in working memory in the face of this distraction. The results suggest that the rehearsal training employed here did improve recall by virtue of encouraging rehearsal strategies, in a way that was not observed among participants receiving interactive imagery training. The fact that these effects were not mediated by age group counts against the view that younger individuals are either unable to rehearse, or show impoverished verbal serial recall because they do not spontaneously engage in rehearsal.